2019
DOI: 10.1017/s0033291719001314
|View full text |Cite|
|
Sign up to set email alerts
|

Equivalency of the diagnostic accuracy of the PHQ-8 and PHQ-9: a systematic review and individual participant data meta-analysis

Abstract: BackgroundItem 9 of the Patient Health Questionnaire-9 (PHQ-9) queries about thoughts of death and self-harm, but not suicidality. Although it is sometimes used to assess suicide risk, most positive responses are not associated with suicidality. The PHQ-8, which omits Item 9, is thus increasingly used in research. We assessed equivalency of total score correlations and the diagnostic accuracy to detect major depression of the PHQ-8 and PHQ-9.MethodsWe conducted an individual patient data meta-analysis. We fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 218 publications
(158 citation statements)
references
References 28 publications
4
139
2
1
Order By: Relevance
“…Differences in classifying participants could similarly reduce the ability to identify potential associations between risk factors and depression. In studies of diagnostic test accuracy, the accuracy of the depression screening tool has been shown to differ across reference standards [33,41,42]. In studies of major depression prevalence, the MINI tends to overestimate compared to the SCID whereas with the CIDI, relative prevalence will depend on the underlying distribution of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in classifying participants could similarly reduce the ability to identify potential associations between risk factors and depression. In studies of diagnostic test accuracy, the accuracy of the depression screening tool has been shown to differ across reference standards [33,41,42]. In studies of major depression prevalence, the MINI tends to overestimate compared to the SCID whereas with the CIDI, relative prevalence will depend on the underlying distribution of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The 8-item Patient Health Questionnaire (PHQ-8) [ 26 ] measures depressive symptoms over the last 2 weeks on a 4-point scale, ranging from 0 (not at all) to 3 (nearly every day) with higher scores (range 0 to 24) indicating more depressive symptoms. The PHQ-8 performs equivalently to the PHQ-9 [ 27 ], which is a valid measure of depressive symptoms in patients with SSc [ 28 ]. The PHQ-8 is available in English and French [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there is no significant difference between PHQ-8 and PHQ-9 versions to discriminate the depressive symptoms (Alpizar, Plunkett, & Whaling, 2018). Wu et al (2019) conducted an individual patient data meta-analysis with 16,742 participants from 54 selected studies. The meta-analysis revealed that the correlation between PHQ-8 and PHQ-9 scores was .996 (95% confidence interval, [0.996, 0.996]).…”
mentioning
confidence: 99%